Clicktivism dalam Perspektif Al-Qur’an: Analisis Tafsir Tematik terhadap Transformasi Sosial Digital - Khoirul Anam; Ikhwanudin; Muhammad Nur Amin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
The development of digital technology has transformed patterns of social participation from conventional activism to social media–based activism known as clicktivism, raising questions about the extent to which such activities contribute to social change and their alignment with Islamic values. This study aims to analyze the phenomenon of clicktivism from a Qur’anic perspective and examine its relevance to social change based on social verses in the Qur’an. The research employs a qualitative approach with a library research design, utilizing the thematic interpretation (tafsir maudhu‘i) method through the collection and analysis of Qur’anic verses related to social themes, supported by classical and contemporary tafsir literature as well as scholarly works on digital activism. The findings indicate that clicktivism is related to Qur’anic values such as amar ma’ruf nahi munkar, ta‘āwun, justice, and social responsibility, and can serve as an initial means of fostering awareness and social participation in the digital era, although it often remains symbolic and not followed by concrete action. This study concludes that clicktivism has the potential to function as a constructive medium for social transformation when accompanied by real actions, making the integration of digital participation and tangible efforts essential for achieving social change in accordance with Qur’anic values.